House of the Surgeon, Pompeii - Anderson, Michael A. (Oxbow Books, 2018)
"The first major publication of one of the largest, most comprehensive, and most important sub-surface, pre-79 AD excavations ever to have been undertaken at Pompeii. This volume concerns the House of the Surgeon and sheds light on the history of Pompeii and situates the results within Roman archaeology"--